2023
DOI: 10.1039/d3cs00328k
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of silver(i)-salts as additives in C–H activation reactions: overall analysis of their versatility and applicability

Renato L. de Carvalho,
Emilay B. T. Diogo,
Simon L. Homölle
et al.

Abstract: This review discusses the important role of silver(i) salts as additives in transition-metal catalyzed C–H activation, and depicts the discussion about the current shift towards Ag-free procedures, as plausible and sustainable alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 240 publications
0
3
0
Order By: Relevance
“…Given the crucial role of silver salts in arylating reactions with iodobenzene substrates, we conducted a screening of various silver salts. 34 The results indicated that silver trifluoroacetate (AgTFA) exhibited the best reaction efficiency. The replacement of Ag 2 CO 3 with AgTFA significantly improved the reaction yield, reaching 72% ( Table 1 , entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Given the crucial role of silver salts in arylating reactions with iodobenzene substrates, we conducted a screening of various silver salts. 34 The results indicated that silver trifluoroacetate (AgTFA) exhibited the best reaction efficiency. The replacement of Ag 2 CO 3 with AgTFA significantly improved the reaction yield, reaching 72% ( Table 1 , entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the reduced Pd(0) species was oxidized to the Pd( ii ) catalyst with the assistance of a stoichiometric amount of silver, which was subsequently used in the next catalytic cycle. 20…”
mentioning
confidence: 99%
“…1 As a consequence, various strategies have been developed for rapid access to intriguing fused compounds, among which transition metal (TM)-catalysed C–H functionalization represents a straightforward protocol due to its high efficiency and remarkable atom-/step-economy. 2 To date, a series of versatile directing groups (DGs) and coupling partners (CPs) have been discovered for addressing the synthesis of complex polycyclic ring-fused structures via a TM-catalysed C–H coupling/cyclization cascade involving the formation of multiple new bonds in a simple one-pot operation, illustrating that the combination of TM-catalysed C–H functionalization and the cascade strategy should be a viable tool for the efficient construction of fused heterocycles. 3…”
mentioning
confidence: 99%